Multi-objective optimization of ultrasound-assisted hybrid drying to preserve rapeseed oil and protein - Khaled Abdeen Mousa Ali; Changyou Li; Mengyao Chen; Zhurong Chen; Zhanhong Huang; Marwa Abd-Elnaby Mohammed; Elsayed Ragab Shousha; Ye Zhang (Journal of Stored Products Research, 2026)

Promising Alginate-Gelatin Scaffolds Containing 5-Fluorouracil and Reinforced with Zinc-Modified Hydroxyapatite: Cell Attachment and One-Year Stability Study - Ebtesam W. Elsayed; Maha F. Emam; Ahmed A. El-Ashmawy; Gehan T. El-Bassyouni; Sahar M. Mousa; Ahmed A. F. Soliman; M. El-Manawaty; Laila H. Emara (Journal of Pharmaceutical Innovation, 2025)
Purpose The current study evaluated the cell attachment capability and long-term stability of 5 - fluorouracil (5-FU) loaded alginate-gelatin scaffolds reinforced with zinc-doped hydroxyapatite (Zn-HA). Methods Zn-HA (2% and 6% Zn) was prepared and evaluated for the crystalline nature, chemical structure, and microstructure of hydroxyapatite (HA). Blank and 5-FU loaded alginate-gelatin-Zn-HA scaffolds were prepared and evaluated in terms of surface area, pore size, pore volume, and morphology using the gas adsorption technique and scanning electron microscopy (SEM). Cell attachment studies were also carried out on normal human cell line. The scaffolds were stored for one year at room temperature and evaluated for any changes in their physico-chemical properties as well as 5-FU release profile. Results The results showed that increasing zinc content decreased HA particle size. The blank scaffolds showed higher surface area, pore volume values, and a less porous structure compared to the drug-loaded ones. The pore size increased after scaffolds soaking in cell-line medium due to the hydrogel-forming materials' biodegradability and drug release. Cell growth on the presoaked drug-loaded scaffolds was improved compared to blank scaffold. XRD, FTIR and 5-FU release profile indicated that the stored scaffolds did not show any physical or chemical changes. Conclusion The prepared scaffolds showed promising results regarding cell attachment capability and long-term stability.

Characterization of the ash samples before and after thermal processing aiming phosphorus extraction and residues valorization - Georgeta Predeanu; Bruno Valentim; Luminita Georgeta Popescu; Alexandru Traian Abagiu; Lucica Anghelescu; Mihaela Niculina Bălănescu; Barbara Białecka; Elza Bontempi; Magdalena Cempa; Marius Florin Drăgoescu; Alexandra Guedes; Özben Kutlu; et al. (International Journal of Coal Geology, 2025)

Enhancing phosphorus recovery from poultry litter ash through microwave-assisted thermochemical treatment for improving its solubility - Ario Fahimi; Mattia Massa; Elsayed Mousa; Guozhu Ye; Georgeta Predeanu; Hayati Olgun; Seyedkamal Mousavinezhad; Ehsan Vahidi; Bruno Valentim; Barbara Białecka; Elza Bontempi (Journal of Environmental Management, 2025)

Quantitative analysis of residual butylated hydroxytoluene and butylated hydroxyanisole in Salmo salar, milk, and butter by liquid chromatography–tandem mass spectrometry - Sara Abdel Basset Galal; Mohammad Madhat Mousa; Eman Saad Elzanfaly; Emad Mohamed Hussien; Enas Abdel Hakim Amer; Hala Elsayed Zaazaa (Food Chemistry, 2024)

A microwave-enhanced method able to substitute traditional pyrometallurgy for the future of metals supply from spent lithium-ion batteries - Ario Fahimi; Ivano Alessandri; Antonella Cornelio; Patrizia Frontera; Angela Malara; Elsayed Mousa; Guozhu Ye; Bruno Valentim; Elza Bontempi (Resources, Conservation and Recycling, 2023)